Fc-based Duokines: dual-acting costimulatory molecules comprising TNFSF ligands in the single-chain format fused to a heterodimerizing Fc (scDk-Fc). (31st December 2022) - Aschmoneit, Nadine; Kocher, Katharina; Siegemund, Martin; Lutz, Martina S.; Kühl, Lennart; Seifert, Oliver; Kontermann, Roland E.
ABSTRACT: Targeting costimulatory receptors of the tumor necrosis factor superfamily (TNFSF) to activate T-cells and promote anti-tumor T-cell function have emerged as a promising strategy in cancer immunotherapy. Previous studies have shown that combining two different members of the TNFSF resulted in dual-acting costimulatory molecules with the ability to activate two different receptors either on the same cell or on different cell types. To achieve prolonged plasma half-life and extended drug disposition, we have developed novel dual-acting molecules by fusing single-chain ligands of the TNFSF to heterodimerizing Fc chains (scDuokine-Fc, scDk-Fc). Incorporating costimulatory ligands of the TNF superfamily into a scDk-Fc molecule resulted in enhanced T-cell proliferation translating in an increased anti-tumor activity in combination with a primary T-cell-activating bispecific antibody. Our data show that the scDk-Fc molecules are potent immune-stimulatory molecules that are able to enhance T-cell mediated anti-tumor responses.